Síntese de zeólitas A e 5A a partir de caulim: uma comparação dos métodos de síntese estático e dinâmico - SANTOS, Suzianny Cristina Arimatéa (Universidade Federal do Pará, 2022)
Greater awareness of environmental issues and policies on conservation have been doing that arise with new proposals for waste recycling. One of those ways is to reuse the employment of the tailing of the beneficiation of kaolin in zeolite synthesis from kaolin tailing, because zeolites have a wide applicability. Zeolite 5A was synthesized by cation exchange using as starting material zeolite A and calcium solution. We have developed a process for synthesis of zeolite A and zeolite 5A, and the kinetic monitoring of obtaining these crystalline phases and scaling of zeolites A and 5A. The following methods were used: XRD, XRF, SEM, DTA-TG and sieve analysis. It was found that using the two methods of synthesis were obtained zeolites A and 5A, but with only variations in the intensities of their peaks, where the synthesized zeolites in dynamic method showed greater intensity and a greater possibility of scaling up production to 400g. The products were used in zeolite adsorption system, the adsorption tests of moisture in the air the same show promise, arriving adsorb up to 20% on the mass of zeolite. It was found that the new dynamic methodology developed for production of zeolite A in this work proved to be much higher than the previous static approach, because it allowed a greater increase in scale beyond the reduction of synthesis time.